A functional MRI study of the relationship between naming treatment outcomes and resting state functional connectivity in post‐stroke aphasia. Issue 8 (22nd January 2014) - van Hees, Sophia; McMahon, Katie; Angwin, Anthony; de Zubicaray, Greig; Read, Stephen; Copland, David A.
Abstract Background The majority of studies investigating the neural mechanisms underlying treatment in people with aphasia have examined task‐based brain activity. However, the use of resting‐state fMRI may provide another method of examining the brain mechanisms responsible for treatment‐induced recovery, and allows for investigation into connectivity within complex functional networks Methods Eight people with aphasia underwent 12 treatment sessions that aimed to improve object naming. Half the sessions employed a phonologically‐based task, and half the sessions employed a semantic‐based task, with resting‐state fMRI conducted pre‐ and post‐treatment. Brain regions in which the amplitude of low frequency fluctuations (ALFF) correlated with treatment outcomes were used as seeds for functional connectivity (FC) analysis. FC maps were compared from pre‐ to post‐treatment, as well as with a group of 12 healthy older controls Results Pre‐treatment ALFF in the right middle temporal gyrus (MTG) correlated with greater outcomes for the phonological treatment, with a shift to the left MTG and supramarginal gyrus, as well as the right inferior frontal gyrus, post‐treatment. When compared to controls, participants with aphasia showed both normalization and up‐regulation of connectivity within language networks post‐treatment, predominantly in the left hemisphere Conclusions The results provide preliminary evidence that treatments for naming impairments affect the FC of language networks, and may aid in understanding the neural mechanisms underlying the rehabilitation of language post‐stroke. Hum Brain Mapp 35:3919–3931, 2014. © 2014 Wiley Periodicals, Inc.